Towards a European integrated financial markets - DINI, L. (PSL Quarterly Review, 2013)
Financial markets around the world are undergoing similar experiences of innovation and conglomeration. This paper reviews those trends and considers the policy implications and the movement towards the integration of the world's capital markets. In particular, the risks and how they can be contained are examined. This leads to an examination of the issues raised by the liberalisation of capital transactions and the implications for the prospects of greater integration of financial markets in Europe. JEL: F36, G15